Osteoporosis Rehabilitation : A Practical Approach - Oleson, Christina V. (Springer International Publishing : Imprint: Springer, 2017)
Taking an expansive perspective on osteoporosis and its ramifications, but with a central focus on the transition from diagnosis to treatment, rehabilitation and current management options, this practical guide discusses the most recent knowledge and literature on osteoporosis for the wide cross-section of professionals involved in treating this pervasive condition. It enables the physician or physician extender to develop a strategy for diagnosing osteoporosis, including detailed laboratory tests as well as imaging, interpreting findings, and determining options appropriate to the needs of individual patients. The material offers guidance on how to treat osteoporosis patients who are suffering from neurological conditions such as brain and spinal cord injuries, rheumatologic syndromes, peripheral neuropathies, gastrointestinal conditions, as well as cardiopulmonary, liver and kidney disorders, among others. Additional chapters address management of osteoporosis in men, patients with advanced medical illnesses including various forms of cancer, organ failure and organ transplantation, pediatric onset of primary and secondary osteoporosis, and the female athlete triad. Covering the gamut of considerations presented by osteoporosis patients, Osteoporosis Rehabilitation: A Practical Approach is a timely, interdisciplinary resource for orthopedists, rehabilitation specialists, primary care physicians, nurses and any other professionals who bring their expertise to bear on the management of this common condition.
Keywords: Medicine.; Endocrinology.; Orthopedics.; Rehabilitation medicine.; elektronické knihy; electronic books